Green synthesis of silver nanoparticles from Cuscuta epithymum extract, evaluation of antibacterial, antioxidant activity, cytotoxic effect on MCF-7 cell line - M. Fereydani; A. Jalalian; N. Saber (MethodsX)
Using plants for the green synthesis of nanoparticles is a cost-effective, non-toxic, and environmentally friendly method. This study synthesized silver nanoparticles using Cuscuta epithymum extract, and their biological activities were evaluated. The C. epithymum extract was prepared by maceration and the synthesis of AgNPs using a green method. Confirmation of AgNPs formation was achieved through UV-Vis and the absorption peak was observed at 425 nm, and their morphology and functional groups were determined by FESEM, TEM, XRD, and FT-IR. The nanoparticles were spherical with a size of 15–60 nm. The antioxidant activity of AgNPs was calculated using the DPPH assay (IC50=45.55 mg/L), and antibacterial properties were obtained by Disk Diffusion methods showed the AgNPs had strong antimicrobial activity. MTT assay showed that the AgNPs caused cytotoxicity in MCF-7 with an IC50=42.53 mg/L, 36.78 mg/L, and 26.86 mg/L (P < 0.0001) after 12, 24, and 48 respectively. It can be concluded that C. epithymum extract can reduce Ag+ ions to silver nanoparticles, which possess excellent antioxidant, antibacterial, and anti-tumor characteristics. • C. epitymum extract could regenerate Ag ions and synthesize silver nanoparticles. • Morphologically investigated by XRD, FESEM, TEM, and FT-IR, their results showed spherical nanoparticles with a 15–60 nm particle size. • Silver nanoparticles had significant antioxidant, antibacterial, and cytotoxic properties.